Genome-wide SNP data support species boundaries in sympatric Polylepis Ruiz & Pav. (Rosaceae) species from Bolivia and Ecuador - Jay Edneil C. Olivar; Marcus Lehnert; Walter Durka; Stefan Michalski; Christiane M. Ritz; Jana Ebersbach; Alexandra N. Muellner-Riehl; Claudia Segovia-Salcedo; Sofía Acosta-Villamarín; Katya Romoleroux; Erika Priscilla Muriel Mera; Emilio J. Trujillo; et al. (Molecular Phylogenetics and Evolution, 2026)

Better alternatives than normalizing to control: case studies with algae toxicity and dose-response analysis - Christian Ritz; Daniel Gerhard; Jens C. Streibig (Environmental and Ecological Statistics, 2026)

Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

Air toxics and late-life dementia and cognitive impairment in Mexican Americans - Yu Yu; Jason Su; Sanjali Mitra; Yufan Gong; Shiwen Li; Yuyuan Lin; Karl O'Sharkey; Kimberly C. Paul; Beate Ritz (Environmental Research, 2025)

Agricultural copper pesticide exposure and DNA methylation in Central Valley of California residents with and without Parkinson's disease - Yufan Gong; Yu Yu; Keren Zhang; Irish Pearl Cambronero Del Rosario; Myles Cockburn; Laura K. Thompson; Adrienne M. Keener; Jeff Bronstein; Beate R. Ritz; Kimberly C. Paul (Environmental Research, 2025)

Challenges in studying air pollution to neurodegenerative diseases - Dayoon Kwon; Kimberly C. Paul; Karl O'Sharkey; Seung-A Paik; Yu Yu; Jeff M. Bronstein; Beate Ritz (Environmental Research, 2025)

DNA methylation biomarkers for cumulative lead exposures and cognitive impairment - Kanghong Shao; Yu Yu; Beate Ritz; Kimberly C. Paul (Environmental Research, 2025)

OS01-04 Review of New Approach Methodologies for application in risk assessment of nanoparticles in the food and feed sector: status and challenges - S.M. Usmani; S. Bremer-Hoffmann; K. Cheyns; F. Cubadda; V.I. Dumit; S.E. Escher; V. Fessard; A.C. Gutleb; T. Léger; Y.-C. Liu; J. Mast; E. McVey; et al. (Toxicology Letters, 2024)

Cost-effectiveness analysis of insecticide ban aimed at preventing Parkinson's disease in Central California - Shiwen Li; Roch A. Nianogo; Yuyuan Lin; Hanwen Wang; Yu Yu; Kimberly C. Paul; Beate Ritz (Science of The Total Environment, 2024)

Neonatal per- and polyfluoroalkyl substance exposure in relation to retinoblastoma - Yixin Chen; Kimberly C. Paul; Douglas I. Walker; Dean P. Jones; Xuexia Wang; Beate R. Ritz; Julia E. Heck (Environmental Research, 2024)

Traffic-related air pollution and Parkinson's disease in central California - Dayoon Kwon; Kimberly C. Paul; Yu Yu; Keren Zhang; Aline D. Folle; Jun Wu; Jeff M. Bronstein; Beate Ritz (Environmental Research, 2024)

Correction to: Higher testosterone and testosterone/estradiol ratio in men are associated with decreased Pheno‑/GrimAge and DNA‑methylation based PAI1 - Cynthia D. J. Kusters; Kimberly C. Paul; Ake T. Lu; Luigi Ferrucci; Beate R. Ritz; Alexandra M. Binder; Steve Horvath (GeroScience, 2023)

Pan-primate studies of age and sex - Steve Horvath; Amin Haghani; Joseph A. Zoller; Ake T. Lu; Jason Ernst; Matteo Pellegrini; Anna J. Jasinska; Julie A. Mattison; Adam B. Salmon; Ken Raj; Markus Horvath; Kimberly C. Paul; et al. (GeroScience, 2023)
Age and sex have a profound effect on cytosine methylation levels in humans and many other species. Here we analyzed DNA methylation profiles of 2400 tissues derived from 37 primate species including 11 haplorhine species (baboons, marmosets, vervets, rhesus macaque, chimpanzees, gorillas, orangutan, humans) and 26 strepsirrhine species (suborders Lemuriformes and Lorisiformes). From these we present here, pan-primate epigenetic clocks which are highly accurate for all primates including humans (age correlation R = 0.98). We also carried out in-depth analysis of baboon DNA methylation profiles and generated five epigenetic clocks for baboons (Olive-yellow baboon hybrid), one of which, the pan-tissue epigenetic clock, was trained on seven tissue types (fetal cerebral cortex, adult cerebral cortex, cerebellum, adipose, heart, liver, and skeletal muscle) with ages ranging from late fetal life to 22.8 years of age. Using the primate data, we characterize the effect of age and sex on individual cytosines in highly conserved regions. We identify 11 sex-related CpGs on autosomes near genes ( POU3F2, CDYL, MYCL, FBXL4, ZC3H10, ZXDC, RRAS, FAM217A, RBM39, GRIA2, UHRF2 ). Low overlap can be observed between age- and sex-related CpGs. Overall, this study advances our understanding of conserved age- and sex-related epigenetic changes in primates, and provides biomarkers of aging for all primates.

Higher testosterone and testosterone/estradiol ratio in men are associated with decreased Pheno-/GrimAge and DNA-methylation based PAI1 - Cynthia D. J. Kusters; Kimberly C. Paul; Ake T. Lu; Luigi Ferruci; Beate R. Ritz; Alexandra M. Binder; Steve Horvath (GeroScience, 2023)
Sex hormones are hypothesized to drive sex-specific health disparities. Here, we study the association between sex steroid hormones and DNA methylation-based (DNAm) biomarkers of age and mortality risk including Pheno Age Acceleration (AA), Grim AA, and DNAm-based estimators of Plasminogen Activator Inhibitor 1 (PAI1), and leptin concentrations. We pooled data from three population-based cohorts, the Framingham Heart Study Offspring Cohort, the Baltimore Longitudinal Study of Aging, and the InCHIANTI Study, including 1,062 postmenopausal women without hormone therapy and 1,612 men of European descent. Sex-stratified analyses using a linear mixed regression were performed, with a Benjamini-Hochberg (BH) adjustment for multiple testing. Sex Hormone Binding Globulin (SHBG) was associated with a decrease in DNAm PAI1 among men (per 1 standard deviation (SD): -478 pg/mL; 95%CI: -614 to -343; P:1e-11; BH-P: 1e-10), and women (-434 pg/mL; 95%CI: -589 to -279; P:1e-7; BH-P:2e-6). The testosterone/estradiol (TE) ratio was associated with a decrease in Pheno AA (-0.41 years; 95%CI: -0.70 to -0.12; P:0.01; BH-P: 0.04), and DNAm PAI1 (-351 pg/mL; 95%CI: -486 to -217; P:4e-7; BH-P:3e-6) among men. In men, testosterone was associated with a decrease in DNAm PAI1 (-481 pg/mL; 95%CI: -613 to -349; P:2e-12; BH-P:6e-11). SHBG was associated with lower DNAm PAI1 among men and women. Higher testosterone and testosterone/estradiol ratio were associated with lower DNAm PAI and a younger epigenetic age in men. A decrease in DNAm PAI1 is associated with lower mortality and morbidity risk indicating a potential protective effect of testosterone on lifespan and conceivably cardiovascular health via DNAm PAI1. Graphical Abstract

Proximity to residential and workplace pesticides application and the risk of progression of Parkinson's diseases in Central California - Shiwen Li; Beate Ritz; Yufan Gong; Myles Cockburn; Aline Duarte Folle; Irish Del Rosario; Yu Yu; Keren Zhang; Emily Castro; Adrienne M. Keener; Jeff Bronstein; Kimberly C. Paul (Science of The Total Environment, 2023)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

Report from the BfR expert hearing on practicability of hormonal measurements: recommendations for experimental design of toxicological studies with integrated hormonal end points - Olena Kucheryavenko; Glenn Lurman; Anja Lehmann; Juliana Braz; Lars Niemann; Ibrahim Chahoud; Alberto Mantovani; Helen Håkansson; Steffen Schneider; Volker Strauss; Pragati S. Coder; Alexius Freyberger; et al. (Archives of Toxicology, 2019)

Type 2 Diabetes Mellitus and Alzheimer’s Disease: Overlapping Biologic Mechanisms and Environmental Risk Factors - Kimberly C. Paul; Michael Jerrett; Beate Ritz (Current Environmental Health Reports, 2018)

Hepatic expression of inflammatory genes and microRNAs in pigs with high “cholesteryl ester transfer protein” (CETP) activity - Susanna Cirera; Benedicte C. Juul Tørsleff; Christian Ritz; Merete Fredholm; Peter M. H. Heegaard; Kerstin Skovgaard (Mammalian Genome, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Of Pesticides and Men: a California Story of Genes and Environment in Parkinson’s Disease - Beate R. Ritz; Kimberly C. Paul; Jeff M. Bronstein (Current Environmental Health Reports, 2016)

Archaeological collagen: Why worry about collagen diagenesis? - R. C. Dobberstein; M. J. Collins; O. E. Craig; G. Taylor; K. E. H. Penkman; S. Ritz-Timme (Archaeological and Anthropological Sciences, 2009)

Chronic low-dose isotretinoin treatment limits renal damage in subtotally nephrectomized rats - Christian Morath; Kerstin Ratzlaff; Claudius Dechow; Vedat Schwenger; Matthias Schaier; Benjamin Zeier; Jörg Peters; Miki Tsukada; Christos C. Zouboulis; Rüdiger Waldherr; Marie-Luise Gross; Eberhard Ritz; et al. (Journal of Molecular Medicine, 2009)

Evolutionary patterns and processes in the genus Rosa (Rosaceae) and their implications for host-parasite co-evolution - V. Wissemann; C. M. Ritz (Plant Systematics and Evolution, 2007)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Phylogeny of subsect. Meleuphorbia (A. Berger) Pax & Hoffm. ( Euphorbia L.) reflects the climatic regime in South Africa - C. M. Ritz; N. F. A. Zimmermann; F. H. Hellwig (Plant Systematics and Evolution, 2003)

Male correlated non-matroclinal character inheritance in reciprocal hybrids of Rosa section Caninae (DC.) Ser. (Rosaceae) - C. M. Ritz; V. Wissemann (Plant Systematics and Evolution, 2003)

Serotonin 2C receptors appear to mediate genetic sensitivity to cocaine-induced convulsions - L. E. O'Dell; M. J. Kreifeldt; F. R. George; M. C. Ritz (Psychopharmacology, 1999)

Contribution of mdr1b-type P-glycoprotein to okadaic acid resistance in rat pituitary GH 3 cells - V. Ritz; K.I. Hirsch-Ernst; I. Quentin; S. Sieder; J. Marwitz; C. Ziemann; H.J. Steinfelder (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Energy and substrate metabolism during a 42-day bed-rest in a head-down tilt position in humans - P. Ritz; K. J. Acheson; P. Gachon; L. Vico; J. J. Bernard; C. Alexandre; B. Beaufrre (European Journal of Applied Physiology, 1998)

Cocaine toxicity: concurrent influence of dopaminergic, muscarinic and sigma receptors in mediating cocaine-induced lethality - M. C. Ritz; Frank R. George (Psychopharmacology, 1997)

Cocaine-induced convulsions: pharmacological antagonism at serotonergic, muscarinic and sigma receptors - M. C. Ritz; Frank R. George (Psychopharmacology, 1997)